PP Smoothing Process Using Green Solvents (Transactions on Additive Manufacturing Meets Medicine, 2023)
Novel surface treatment for Additively Manufactured Polypropylene parts is presented in this work for potential uses in medical applications. The method uses green sustainable solvent to smooth, seal and remove semi-sintered powder particles from the surface. The new surface smoothing with given solvent produces parts that can be used in medical applications. Optical microscope images of the smoothed part showed disappearance of the semi-sintered powder particles and surface pores, which were largely visible on the unprocessed part. The smoothed PP parts were seen to have better performance properties, both mechanically and aesthetically. Cytotoxicity results showed that the smoothed PP parts have no cytotoxic effect.
Keywords: 3D Printing; Additive Manufacturing; Polypropylene; postprocessing; surface; Medicine